Aeroplane design studies conventional and V.T.O.L. freighter aircraft (Academic Years 1959 and 1961) - Howe, D. (College of Aeronautics, 1963)
During the second year of their course in the Department of Aircraft Design, students have the option of working as a member of a team engaged in a design study. The subjects for the studies are chosen to represent the current interests of the industry and include unusual features considered to be worthy of investigation. Examples of these design studies are the F-59 freighter and its derivative the F-61, V. T.O. L. freighter. In a conventional role these designs are intended to carry a payload of up to 77000 lb. , over 800 nautical miles range, using four turboprop engines. V. T.O. L. capability is given to the F-61 design by the addition of two wing pods, each of which houses 22 lift engines. The application of boundary layer control in the form of blown ailerons and flaps has been investigated for the F-59 design. Both aircraft have been designed in detail. The major conclusion of the studies is that the application of V. T.O. L. to large freight aircraft is feasible, but further detailed work is necessary to resolve some flutter and noise problems.